Pollution of the atmospheric air of the city of Balkhash with heavy metals - Nurlybayeva К.А.; Mukasheva, G.Zh.; Sarsembayeva, A.Sh. (Fundamental and Experimental Biology, 2022)
The article discussed the situation of atmospheric air pollution in the city of Balkhash with chemical elements. The size of suspended particles according to the results of stationary observation of the RM-10 sample was 0.8 MPC with a concentration of dust particles (dust/aerosol, not differentiated by composition) of 99.6%. The norm is 0.05 mg/m3, the maximum single concentration of solid particles in the atmospheric air of the city of Balkhash was 0.2 MPC. The size of RM is 2.5 concentration of suspended particles. According to the norms, the average daily level of RM 2.5 should not exceed 0.25 mg/m3. Based on our data, the average daily level of RM 2.5 was the maximum RM-2.5 - 0.2 MPC of a single concentration of solid particles with a multiplicity exceeding 0.7 mg/m3. The average concentration of ozone in the whole city is 1.5 MPC s.s. sulfur dioxide -5.4 MPC m.r.k.; carbon monoxide-2.2 MPC m.r.k; nitrogen dioxide -2.0 MPC m.r.k.; hydrogen sulfide - 20.1 mpc.R.K. It was found that at the maximum permissible single concentration of 0.5 mg/m3, the actual concentration of sulfur dioxide during adverse meteorological conditions exceeded the corresponding MPC by 23.7 times.